Enhanced Cellular Uptake and Photodynamic Effect with Amphiphilic Fluorinated Porphyrins: The Role of Sulfoester Groups and the Nature of Reactive Oxygen Species - Pucelik, Barbara (2020)
A class of amphiphilic photosensitizers for photodynamic therapy (PDT) was developed. Sulfonate esters of modified porphyrins bearing-F substituents in the ortho positions of the phenyl rings have adequate properties for PDT, including absorption in the red, increased cellular uptake, favorable intracellular localization, low cytotoxicity, and high phototoxicity against A549 (human lung adenocarcinoma) and CT26 (murine colon carcinoma) cells. Moreover, the role of type I and type II photochemical processes was assessed by fluorescent probes specific for various reactive oxygen species (ROS). The photodynamic effect is improved not only by enhanced cellular uptake but also by the high generation of both singlet oxygen and oxygen-centered radicals. All of the presented results support the idea that the rational design of photosensitizers for PDT can be further improved by better understanding the determinants affecting its therapeutic efficiency and explain how smart structural modifications can make them suitable photosensitizers for application in PDT.